2022
DOI: 10.1001/jamanetworkopen.2022.23033
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Weekly National Opioid Overdose Deaths in Near Real Time Using Multiple Proxy Data Sources

Abstract: IMPORTANCEOpioid overdose is a leading public health problem in the United States; however, national data on overdose deaths are delayed by several months or more. OBJECTIVES To build and validate a statistical model for estimating national opioid overdose deaths in near real time. DESIGN, SETTING, AND PARTICIPANTS In this cross-sectional study, signals from 5 overdoserelated, proxy data sources encompassing health, law enforcement, and online data from 2014 to 2019 in the US were combined using a LASSO (least… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 30 publications
2
14
0
Order By: Relevance
“…18 Although machine learning models are increasingly being used to forecast and study infectious diseases (eg, influenza-like illness 28 and COVID-19 29 ), applying these methods to noninfectious diseases is recent. 10,14 Reporting of infectious diseases is much faster than for noninfectious diseases (eg, 1-2 weeks for influenza 30 Researching the utility of other data sources, such as news reports, social media, and information collated by the Gun Violence Archive, 26 would also be beneficial.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…18 Although machine learning models are increasingly being used to forecast and study infectious diseases (eg, influenza-like illness 28 and COVID-19 29 ), applying these methods to noninfectious diseases is recent. 10,14 Reporting of infectious diseases is much faster than for noninfectious diseases (eg, 1-2 weeks for influenza 30 Researching the utility of other data sources, such as news reports, social media, and information collated by the Gun Violence Archive, 26 would also be beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…Although machine learning models are increasingly being used to forecast and study infectious diseases (eg, influenza-like illness and COVID-19), applying these methods to noninfectious diseases is recent . Reporting of infectious diseases is much faster than for noninfectious diseases (eg, 1-2 weeks for influenza vs 1 year for topics such as suicide and firearm injury); as a result, infectious disease models use the previous week’s standard data (eg, infection rates, hospitalizations, and deaths) to build timely forecasts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two studies explored the relationship between drug-related internet search queries and opioid-related emergency department (ED) visits in the United States, and both demonstrated the predictive potential of internet search data [12,13]. Three further studies found strong associations between drug-related internet search queries and opioid-related overdose deaths at the national, state, and county levels [14][15][16]. Elsewhere, studies have demonstrated the potential use of opioid-related data from social media platforms, including Twitter and Reddit, to inform surveillance efforts [17][18][19].…”
Section: Introductionmentioning
confidence: 99%